Hubungan antara Perilaku Seksual dan Menarche Dini pada Remaja Indonesia - Laura Nadya Damayanty Agusputri; Cornelius Youwena; Lutfi Agus Salim (Media Gizi Kesmas, 2023)
Background: Menstruation is one of the signs that a woman is entering adolescence. Menarche is the first menstrual event in women which generally occurs at the age of 12 to 15 years. An increase in the number of adolescents who experience menarche before the age of 12 years occurs in several countries. Sexual behavior in adolescents that can be positive or negative can be the reason for the increase and development of hormones in the human body. Objectives: The study was conducted to determine the relationship between sexual behavior and the incidence of early menarche in adolescent girls in Indonesia in 2017. Methods: The study is a quantitative descriptive study with a cross sectional research design using secondary data obtained from the 2017 Indonesian Demographic and Health Survey (IDHS) conducted in 34 provinces in Indonesia starting on July 24 and ending on December 30, 2017. The sample in this study was 1,494 adolescent girls in Indonesia with the age of 15 years, unmarried, and already experiencing menstruation. The variables involved in this study were sexual behavior and the incidence of early menarche in adolescent girls in Indonesia in 2017. Data analysis in this study used bivariate analysis by displaying frequency distribution tables along with analysis tables with chi-square tests. Results: The majority of respondents (71.2%) in this study had high-risk sexual behavior, the incidence of early menarche in adolescents aged â‰¤13 years was 77.4% and the p-value <0.05 on the relationship between sexual behavior and the incidence of menarche in adolescent girls in Indonesia in 2017. Conclusions: This study shows that there is an association between sexual behavior and the incidence of early menarche in adolescent girls in Indonesia. Education and parental supervision of sexual relationships and behavior in adolescents need to be done to minimize the incidence of early menarche in adolescent girls in Indonesia.